A novel automated kinematic capillary viscometer system for precise viscosity measurements - Amer Mohammed Bin Hajeb; Syamsul Rizal Abd.Shukor; Yusoff Azudin Nurhazwani; Jin Xue Soo; Kai Yuan Saw; Shaer Jin Liew; Chiat Oon Tan; Chiat Soon Tan (Springer Berlin Heidelberg, 2025)
This study explores recent advancements in viscometry techniques for precise viscosity measurements, focusing on automating the widely used Unbeholden capillary viscometer. Previous attempts at automation utilizing single-camera and infrared laser techniques demonstrated initial promise; however, these approaches exhibited significant limitations. This research introduces the design and validation of a new automated kinematic capillary viscometer system utilizing real-time computer vision for simultaneous meniscus detection and timing up to three viscometers. The system incorporates two waterproof cameras per Unbeholden viscometer connected to a computer running custom-made Visco Check software, with temperature control managed by an Arduino microcontroller. It maintains the water bath temperature within ± 0.5 °C and measures flow time with ± 0.01 s resolution. The system was validated by measuring the viscosity of a binary ethanol–hexane mixture across the entire mole fraction range at a constant pressure of 101.325 kPa and a temperature of 298.15 K. Results were compared with literature values and correlated using the Grunberg–Nissan (G–N) and McAllister three-body models. Excess molar volumes (V E) and viscosity deviations (Δï) were calculated to assess accuracy in capturing complex liquid mixture behavior. Findings revealed general agreement between experimental and reference data. The G–N model showed excellent agreement, exhibiting a low standard deviation (0.036) and absolute average deviation (1.648%). These results demonstrate the system’s potential as a reliable tool for precise automated viscosity measurements across various industrial applications